Analisis Hubungan Rantai Pasok Terhadap Kualitas Rumput Laut di Kabupaten Bantaeng - Tahir, Rahmawati; Mundiyah, A Iva (Journal Galung Tropika, 2020)
The government’s demand to improve the quality of production and business development not in accordance with a condition of development of seaweed cultivation in Bantaeng Regency, South Sulawesi as a center for seaweed development, which is still relatively low. The low production and quality were influenced by various factors. This study aims were to identify the structure of the seaweed supply chain, analyze post-harvest handling, and describe the quality of seaweed in Bantaeng Regency. The total sample of 27 respondents taken by purposive sampling. This research used a qualitative descriptive approach and SWOT analysis. The results showed that the seaweed supply chain business actors in Bantaeng Regency were still in the open market negotiation process with their respective roles. Farmers play a role in seaweed farming activities, traders collectors play a role as an intermediary for information. Providers of capital for farmers and the quality of seaweed in this area is still relatively low.